2013
DOI: 10.1159/000343367
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-2 and JNK Activated by Saturated Fatty Acids are Not Involved in Apoptosis Induction but Modulate ER Stress in Human Pancreatic �-cells

Abstract: Background: Fatty acid-induced apoptosis and ER stress of pancreatic β-cells contribute to the development of type 2 diabetes, however, the molecular mechanisms involved are unclear. Aims: In this study we have tested the role of caspase-2 and suggested ER stress mediator JNK in saturated fatty acid-induced apoptosis of the human pancreatic β-cells NES2Y. Results: We found that stearic acid at apoptosis-inducing concentration activated ER stress signaling pathways, i.e. IRE1α, PERK and ATF6 pathways, in NES2Y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 43 publications
3
40
0
1
Order By: Relevance
“…We are proceeding to describe that endogenous production of stearic acid was increased while total MUFA (oleic acid and palmitoleic acid) was decreased in the pancreas of diabetic rats. These findings align with other studies showing that stearic acid induced endoplasmic reticulum stress of pancreatic β-cells [60]. In fact, a substantial increase in stearic acid content of pancreatic islets incubated in the presence of glucose had been previously reported [61].…”
Section: Discussionsupporting
confidence: 93%
“…We are proceeding to describe that endogenous production of stearic acid was increased while total MUFA (oleic acid and palmitoleic acid) was decreased in the pancreas of diabetic rats. These findings align with other studies showing that stearic acid induced endoplasmic reticulum stress of pancreatic β-cells [60]. In fact, a substantial increase in stearic acid content of pancreatic islets incubated in the presence of glucose had been previously reported [61].…”
Section: Discussionsupporting
confidence: 93%
“…The cells were cultured in a medium based on the RPMI 1640 (Sigma-Aldrich, St. Louis, MO, USA) containing phenol red, extra L-glutamine (300 μg/ml), sodium pyruvate (110 μg/ml), HEPES (15 mM), penicillin (100 U/ml) and streptomycin (100 μg/ml), as previously described [29,30]. The medium was also supplemented with 10% heat-inactivated fetal bovine serum (Biochrom AG, Berlin, Germany).…”
Section: Cells and Cell Culture Conditionsmentioning
confidence: 99%
“…Hyperlipidaemia, in turn, is typically associated with elevated non-esterified fatty acid (NEFA) plasma concentrations, which are supposed to contribute to insulin resistance, impaired insulin secretion due to a progressive decline in pancreatic β-cell function and mass, a phenomenon called lipotoxicity [5][6][7]. In vitro studies have shown that long-chain saturated NEFAs can induce apoptosis [8][9][10][11]. This has been considered, at least in part, to be mediated by the induction of the unfolded protein response (UPR) [12].…”
Section: Introductionmentioning
confidence: 99%